Modeling of test structures for applications in EM shielding - Lim, York Ying (2015)
The next generation of components and devices are reduced in size, which makes the circuit more compact that will affect the signal integrity. One of the current techniques used for RF isolation is by implementing via fence guard trace in compact circuitries to isolate near end interference. However, it is not possible to reduce the distance between guard trace and transmission lines without affecting the level of crosstalk isolation. In recent years, carbon nanotubes (CNTs) are attractive in circuit devices for electromagnetic interference shielding due to its high current density, flexibility, high tensile strength and high thermal conductivity. In this work, design test structures of microstrip, guard trace and guard trace with CNT wall were modeled and simulated. Simulations of CNTs are limited to 1 mm in this scope of work. Additional of a thin layer of metal on the CNT wall shown improvement in crosstalk isolation. Another simulation was done with CNT lid and Ag lid, SE differences were observed from 1-15 GHz.